2016
DOI: 10.17140/whoj-1-110
|View full text |Cite
|
Sign up to set email alerts
|

Mother’s Experiences and Perceptions of a Continuous Caring Model with Fathers after Caesarean Section: A Qualitative Study

Abstract: CitationOne theme family friendly practice after caesarean section and four categories. Mothers described the benefits of this model of caring. The fathers presence was important to mother and baby. Mothers were reassured that the baby was not left alone with staff. It was important for the mothers to see that the father could love the baby as much as the mother. This model of care helped create ties between the father and newborn during the period of mother-infant separation and later with the mother. Conclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Another study from the same sample and hospital setting showed that fathers who took care of their newborn infants for the first hours after birth developed a better understanding of their infant's first moments of life and became more engaged with them as a result 15 . Another paper on the same cohort reported that the mothers felt that the family benefitted from the fathers caring for their newborn infant while they recovered from their Caesarean section and were separated from their baby 16 …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Another study from the same sample and hospital setting showed that fathers who took care of their newborn infants for the first hours after birth developed a better understanding of their infant's first moments of life and became more engaged with them as a result 15 . Another paper on the same cohort reported that the mothers felt that the family benefitted from the fathers caring for their newborn infant while they recovered from their Caesarean section and were separated from their baby 16 …”
Section: Discussionmentioning
confidence: 97%
“…15 Another paper on the same cohort reported that the mothers felt that the family benefitted from the fathers caring for their newborn infant while they recovered from their Caesarean section and were separated from their baby. 16 These findings about paternal newborn care are important because many countries routinely separate both parents from their newborn infant after Caesarean sections. This is particularly true in low-income and middle-income countries.…”
Section: Discussionmentioning
confidence: 99%
“…Childhood illness and hospitalization is a crisis and can cause anxiety for parents and children (6)(7)(8). Parents of these children face numerous difficulties while taking care of their children, which would have a great impact on their health (1,9). One of the main causes of parents' anxiety that affects their mental health is inadequate parental knowledge of how to care for a hospitalized child.…”
Section: Introductionmentioning
confidence: 99%